Implementasi pemahaman dan kesiapan SAK EMKM pada UMKM Giri Sembada - Dinda Muchlis Mustarini; Rigel Nurul Fathah (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2023)
SAK EMKM was created in January 1, 2018 to fulfill financial reports for micro, small and medium entities. The purpose of this study is to analyze the understanding and readiness of MSMEs in implementing SAK EMKM-based financial reports in Girikerto-Turi. This study uses qualitative methods. The subjects of this study are 11 business actors who already have an IUMK in the Girikerto area. The results of the study show that MSME actors in Girikerto have understood basic accounting, namely micro businesses 70.7% and small businesses 81.8%. For the understanding of SAK EMKM, business actors do not understand, namely about 54,2% of micro businesses and 68.75% of small businesses. MSME managers stated that they are ready to implement, which is around 65.1% for micro businesses and 57.1% for small businesses. The hope is for the authorities to carry out socialization, training, and assistance regarding SAK EMKM so that business actors can practice financial reporting better.